The Lincoln mailbag : America writes to the President, 1861-1865 - Holzer, Harold; Lincoln, Abraham, 1809-1865. (Carbondale, Ill. : Southern Illinois University Press, 1998)
"As president, Abraham Lincoln received between two hundred and five hundred letters a day--correspondence from public officials, political allies, and military leaders, as well as letters from ordinary Americans of all races who wanted to share their views with him. Here, and in his critically acclaimed volume Dear Mr. Lincoln, editor Harold Holzer has rescued these voices--sometimes eloquent, occasionally angry, at times poetic--from the obscurity of the archives of the Civil War. The Lincoln Mailbag includes letters written by African Americans, which Lincoln never saw, revealing to readers a more accurate representation of the nation's mood than even the president knew. This first paperback edition of The Lincoln Mailbag includes a new index and fourteen illustrations, and Holzer's introduction and annotations provide historical context for the events described and the people who wrote so passionately to their president in Lincoln's America."--EBSCO
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Lincoln, Abraham, -- 1809-1865 -- Correspondence; Lincoln, Abraham, -- 1809-1865; United States -- History -- Civil War, 1861-1865 -- Sources; HISTORY; United States; Amerikaanse burgeroorlog; Publieke opinie; Sociale situatie; 1861-1865; History; Personal correspondence; Sources